2008
DOI: 10.1210/en.2007-1245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glutathione Depletion on Leydig Cell Steroidogenesis in Young and Old Brown Norway Rats

Abstract: Changes in the oxidant/antioxidant environment of aging Leydig cells have been shown to be correlated with the reduced ability of these cells to produce testosterone. With this in mind, we hypothesized that the experimental depletion of glutathione (GSH), an abundant Leydig cell intracellular antioxidant, might result in reduced testosterone production. Incubation of Leydig cells isolated from the testes of adult Brown Norway rats with buthionine sulfoximine (BSO) reduced GSH content by more than 70% and testo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…Leydig cells, which reside in the testicular interstitium, are reported to be particularly suscepti- ble to oxidative damage in vivo due to their close proximity to reactive oxygen species-producing testicular interstitial macrophages (44). Decreased antioxidant enzyme activities, gene expression, and protein levels, along with lower glutathione, have been reported to play a key role in the diminished ability of Leydig cells from aging rat populations to synthesize testosterone (43,(45)(46)(47). Other work showed that steroidogenic luteal cells in vitro became damaged and dysfunctional when exposed to cumene hydroperoxide or a fatty acid hydroperoxide (48).…”
Section: Discussionmentioning
confidence: 99%
“…Leydig cells, which reside in the testicular interstitium, are reported to be particularly suscepti- ble to oxidative damage in vivo due to their close proximity to reactive oxygen species-producing testicular interstitial macrophages (44). Decreased antioxidant enzyme activities, gene expression, and protein levels, along with lower glutathione, have been reported to play a key role in the diminished ability of Leydig cells from aging rat populations to synthesize testosterone (43,(45)(46)(47). Other work showed that steroidogenic luteal cells in vitro became damaged and dysfunctional when exposed to cumene hydroperoxide or a fatty acid hydroperoxide (48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GSH is involved in Leydig cell steroidogenesis (Diemer et al, 2003;Chen et al, 2008). Here, we wondered whether stimulation of GSHmediated progesterone production and the anti-apoptotic effect in preovulatory GCs exposed to arsenite.…”
Section: Activation Of Caspase-3 Regulates Progesterone Production Inmentioning
confidence: 99%
“…Thus, we can conclude that the protective effect of arsenite on GCs can be partially due to GSH production augmented by progesterone. Both ROS and the depletion of GSH inhibit steroidogenesis in Leydig cells (Diemer et al, 2003;Chen et al, 2008). Chen et al (2010) reported that GSH depletion by BSO led to significant reductions of progesterone level in MA-10 Leydig cells exposured to the pro-oxidant tert-butyl hydroperoxide (t-BuOOH), although BSO alone did not affect progesterone production.…”
Section: Journal Of Cellular Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of deficits have been identified in the steroidogenic pathway of old Leydig cells that might account for the reduced LH-stimulated testosterone production, including reductions in cAMP production, steroidogenic acute regulatory protein (STAR), translocator protein (TSPO), cholesterol translocation from the cytosol into the mitochondria, cholesterol metabolism to pregnenolone in the mitochondria, and downstream steroidogenic enzymes of the mitochondria and smooth endoplasmic reticulum (Culty et al, 2002; Leers-Sucheta et al, 1999; Liao et al 1993; Luo et al, 2005, 2001, 1996; Zirkin and Chen, 2000). Although the mechanism by which these changes occur remains uncertain, imbalance between the production of reactive oxygen species (ROS) and intracellular antioxidant defenses has been proposed (Cao et al, 2004; Chen et al, 2001, 2008; Chen and Zirkin, 1999; Lacombe et al, 2006; Luo et al, 2006). …”
Section: Introductionmentioning
confidence: 99%